Sounding Traumatic Memory - Martin Ringsmut (Music & Minorities)
This article examines the significance of music as a medium of memory in the broader context of Romani World War II remembrance and human rights activism of the last decade. It specifically focusses on the oratorio Symphonia Romani – Bari Duk by Adrian Gaspar and the documentary film Dui Rroma by Gaspar’s mother Iovanca Gaspar as memory media (Erll 2011a) of the Roma genocide during World War II. The composer based the libretto of the Symphonia Romani on a series of interviews conducted with the late survivor of the National Socialist genocide of Sinti and Roma, Hugo Höllenreiner, reflecting key moments of his memories of Auschwitz. In turn, the documentary Dui Rroma explores the relationship between the Sinto Höllenreiner and the Rom Gaspar and provides further information about Höllenreiner’s life and the Nazi persecution of Sinti and Roma during World War II as well as the genesis of Gaspar’s musical work until its premier in 2011. This article analyses the lyrical and musical contents of the oratorio (and the documentary as an extension of that work) with respect to their role in sounding traumatic memories. My findings are based on ethnographic fieldwork and multiple in-depth interviews with the composer and film director since 2017. I set these in dialogue with current key concepts from the field of memory studies, which consider memory as a cultural practice (Rigney 2015) that involves “movement” (Erll 2011b). Highlighting the different positionalities involved in sounding traumatic memories of Sinti and Roma to a largely non-minority audience, I emphasise the translations and transformations of memory in these processes. Central to this analysis are conceptualisations of the “witness” (Assmann 2016) and the transition from memory to postmemory (Hirsch 2012). This article argues from the standpoint of the emerging field of musical memory studies (Spinetti, Schoop, and Hofman 2021) and aims to bridge the gap between the fields of (ethno)-musicology, minority studies, and memory studies.